Pengaruh Pembelajaran Adaptif dan Pembelajaran Demokratis terhadap Kinerja Mengajar Guru PNS se Kabupaten Mojokerto - Happy Ikmal (PROGRESSA: Journal of Islamic Religious Instruction, 2018)
Adaptive challenges require re-orientation of thinking and operation, the gap between aspiration and reality is closed when they learn new ways, in addition to adaptive teaching, there is also democratic teaching, democratic teachers must respect the rights of students, including the right to be guided, to be humanized. The purpose of this research are: 1) To know whether Adaptive learning and democratic learning have an effect simultaneously on teaching performance of teacher 2) To know whether adaptive learning and democratic learning have partial influence on teachers' teaching performance 3) To know which of them is most dominant influence among adaptive learning organizations. And democratic learning on teacher teaching performance. This research uses quantitative description analysis with explanatory research, Number of subjects in population 385 people. Sampling method using saturated sampling. In this study the authors use multiple linier regression analysis techniques. The technique, described briefly among variables. From the research results can be summarized as follows: 1) Adaptive learning and democratic learning effect simultaneously on teacher teaching performance. 2) Adaptive learning and parochial learning partially affect teacher teaching performance. 3) Democratic learning has the most dominant influence on teachers' teaching performance.